The Application of Interactive Learning Methods in English Class (A Survey at SMK Teknologi Muhammadiyah Limboto) - Nur Diva Hanafi; Yuwin Rustam Saleh; Adimawati Helingo; David Kaunang (Ma'soem University, 2026)
This research aims to investigate the application of interactive learning methods in English classes and identify the challenges faced by teachers at SMK Teknologi Muhammadiyah Limboto. As vocational students require practical communication skills, the study explores how teachers bridge the gap between student passivity and active engagement in the classroom. This study employed a qualitative survey method. Data were collected through classroom observations and semi-structured interviews with English teachers, then analyzed using thematic analysis to identify recurring patterns in teaching strategies and classroom dynamics. The findings reveal that teachers actively implement various interactive methods, including Project-Based Learning, Role-Playing, Group Discussions, Storytelling, and Debates. These activities are supported by digital tools such as Flip, Padlet, Quizizz, and Kahoot to foster a collaborative learning environment. However, the implementation faces several challenges, specifically time constraints, disparities in student abilities, and limited infrastructure. Teachers overcome these obstacles through adaptive strategies like cooperative learning and the utilization of simple technology. The study concludes that while challenges exist, interactive learning effectively promotes critical thinking and communication skills, suggesting a need for continued pedagogical adaptation and facility support in vocational education.